Targeting the ROCK2/UBA52/DRP1 axis enhances ferroptosis and overcomes pemigatinib resistance in Cholangiocarcinoma - Bolin Zhang; Shan Lu; Xin Xiao; Yushu Xu; Shouhua Zhang; Leifeng Chen; Wei Zhou (Cell Death and Disease)
Abstract Cholangiocarcinoma (CCA) is a highly aggressive cancer that arises from the bile duct and has an extremely poor prognosis. Pemigatinib is the only Food and Drug Administration (FDA)-approved CCA-targeted drug. The CCA treatment options are insufficient considering its poor prognosis and increasing morbidity. Recently, Rho-associated coiled-coil containing protein kinase 2 (ROCK2) has been reported to promote resistance to chemotherapy. In this study, we investigated the role that ROCK2 plays in the development of resistance of CCA cells to Pemigatinib. Here, we developed Pemigatinib-resistant CCA cells, performed mRNA sequencing, retrieved The Cancer Genome Atlas (TCGA) data, and analysed ROCK2 expression in a large CCA cohort. The expression level of ROCK2 in CCA cells was significantly higher than that in adjacent noncancerous tissues. Increased expression of ROCK2 in CCA was related to a late TNM stage and decreased overall survival. Functional experiments revealed that downregulating the expression of ROCK2 promotes the ferroptosis of CCA cells, and enhances sensitivity to Pemigatinib. Moreover, upregulation of ROCK2 increased the expression of Drp1 protein. The effect of downregulating ROCK2 was reversed by Drp1 overexpression, and Drp1 knockdown inhibited Ferroptosis driven by ROCK2 overexpression. Mechanistically, ROCK2 stabilized the expression of Drp1 by competing with UBA52 to bind Drp1 and inhibiting the ubiquitination-mediated degradation of Drp1. Blocking of the UBA52– Drp1 axis inhibited the antitumour effect of Pemigatinib in ROCK2-knockdown cells both in vitro and in vivo. In conclusion, the ROCK2/UBA52/Drp1 axis is a pivotal driver of Pemigatinib resistance in CCA cells. These results provide novel insights into Pemigatinib resistance in CCA cells, suggesting that ROCK2 is a promising therapeutic target for the treatment of CCA.